Postcolonial and Multicultural Analysis of Gender-Sexuality Representation in the Film “Gowok: Kamasutra Jawa” - Sari, Atika (LifeSciFi, 2025)
The phenomenon of interracial romantic relationships and beauty standards in Indonesia reflects a colonial legacy that constructs white skin as a symbol of superiority and marginalizes dark skin, a condition often reproduced through film as a medium that shapes gender and sexuality discourse. The film Gowok: Javanese Kamasutra, which depicts traditional Javanese sexual education through female characters, serves as an important space for examining implicit racial and cultural inequalities. This study aims to analyze the representation of gender and sexuality in the film using a postcolonial and multicultural approach, particularly regarding interracial relations and biased beauty standards. The method used is qualitative, with content analysis of the film based on synopses and reviews, and secondary data from social media, especially TikTok, which discusses similar issues. The main findings indicate that interracial romantic relationships still reproduce the fetishization of Indonesian women’s bodies as exotic objects, while the narrative of “beautiful is white” remains dominant as a continuation of colonial values. This study contributes by emphasizing the important role of media in dismantling historical power structures, breaking down colonial stereotypes, and encouraging more inclusive cultural practices to build a just and diverse Indonesian society.